Dual Reporting of Clostridioides difficile PCR and Predicted Toxin Result Based on PCR Cycle Threshold Reduces Treatment of Toxin-Negative Patients without Increases in Adverse Outcomes - Hitchcock, Matthew M. (J Clin Microbiol, 2019)
Nucleic acid amplification tests are commonly used to diagnose Clostridioides difficile infection (CDI). Two-step testing with a toxin enzyme immunoassay is recommended to discriminate between infection and colonization but requires additional resources. Prior studies showed that PCR cycle threshold (C(T)) can predict toxin positivity with high negative predictive value. Starting in October 2016, the predicted toxin result (CT-toxin) based on a validated cutoff was routinely reported at our facility. To evaluate the clinical efficacy of this reporting, all adult patients with positive GeneXpert PCR results from October 2016 through October 2017 underwent a chart review to measure the recurrence of or conversion to a CT-toxin(+) result and 30-day all-cause mortality. There were 482 positive PCR tests in 430 unique patients, 282 CT-toxin(+) and 200 CT-toxin(−). Patient characteristics were similar at testing, though CT-toxin(+) patients had higher white blood cell (WBC) counts (12.5 × 10(3) versus 9.3 × 10(3) cells/μl; P = 0.001). All cases (n = 21) of fulminant CDI had a CT-toxin(+) result. Index CT-toxin(+) patients were significantly more likely to have a CT-toxin(+) result within 90 days than CT-toxin(−) patients (17.4% [n = 49] versus 8.0% [n = 16], respectively; P = 0.003). Thirty-day all-cause mortality was higher in CT-toxin(−) patients (11.1% versus 6.8%; P = 0.1), though no deaths in CT-toxin(−) patients were directly attributable to CDI. Of the 200 CT-toxin(−) patients, 51.5% (n = 103) were treated for CDI. The rates of conversion to a CT-toxin(+) result (8.8% versus 7.2%; P = 0.8) and all-cause mortality (8.8% versus 13.4%; P = 0.3) were similar between treated and untreated CT-toxin(−) patients, respectively. C(T)-based toxin prediction may identify patients at higher risk for CDI-related complications and reduce treatment among CT-toxin(−) patients.